High Sensitivity Non-split Drain MAGFET for Wireless Sensor Networks - Rattapong Nakachai; Amporn Poyai; Toempong Phetchakul (My University, 2020)
The non-split drain MAGFET proposed in this paper is aspossess an ideal, highest sensitivity in the same type of device, current mode for low power, and low voltage that can be embedded within a system for wireless sensor networks application. It is a split-drain MAGFET that is designed to have no gap between drains so that there is no loss from the gap. There are two split contacts in one drain to represent the split drains for current difference that induced from due to magnetic field. The relative sensitivity comparison among all the gaps (3, 2, 1, and 0 μm) with all aspect ratio of width (W)/length (L) (L/W = 1, 0.6, and 0.2) at biased current 0.25 mA shows that the zero gap or the non-split drain MAGFET structure gives the highest sensitivity. The sensitivities of the non-split drain at the aspect ratios L/W = 1, 0.6, and 0.2 in this study are 0.0595, 0.0479, and 0.0231 T−1, respectively. It is proved that the gap is not necessary for the MAGFET. It is a new, smart way to design the MAGFET for the highest sensitivity and gap lossless for modern sensor applications.
Keywords: Magnetic Field Sensors Techniques